Sistema natural, luz e nutrição em plântulas de Saccharum officinarum in vitro - Silva, Jefferson Henrique Santos (2023)
Sugarcane is one of the main crops in Brazil, planted in almost the entire territory and adapted to the different regions of the country. The objective of this work was to evaluate the influence of the natural ventilation system, light intensity, light spectrum and composition of the culture medium on the in vitro cultivation of sugarcane. Lateral shoots were cultivated in MS medium and maintained in a completely randomized design (DIC). Article I - 3x3 double factorial scheme, with three numbers of explants per flask (5, 10 and 20) and three ventilation systems (Without filter - SC, with two filters - SVN2 and four filters - SVN4). Article II - kept under five light intensities: 26, 70, 100, 113 and 144 μmol m−2 s−1 and under different light spectra: monochromatic white; red; blue and combinations of blue - %A and red - %V: (30:70; 70:30; and 50:50). Article III - reduction of the original concentration of NH4NO3 and KNO3 salts, in percentage and light intensity, with three concentrations of NH4NO3 and KNO3 (25, 50 and 100%) and five light intensities (26, 70, 100, 113 and 144 μmol m−2 s−1). The third experiment also consisted of increasing the original concentration of CaCl.2 and MgSO4 salts (100, 200 and 400%) and pH variations (5.50; 5.75 and 6.00). After 35 days of in vitro cultivation, agronomic growth parameters and photosynthetic pigments were evaluated. There was less accumulation of dry mass with the increase in the number of explants per flask. For the agronomic growth parameters, the natural ventilation system with four filters and 5 explants per flask provided greater gains. However, the natural ventilation system with four filters, 10 and 20 explants per flask resulted in accumulation of seedling dry mass, which favored plant growth during the acclimatization phase. The use of porous membranes in the micropropagation of sugarcane with 10 and 20 explants per flask can be recommended. The light intensity of 113 μmol m−2 s−1 resulted in the highest production of dry mass and photosynthetic pigments, providing the highest seedling vigor. The white, blue and red monochromatic light spectra resulted in seedlings with higher dry mass accumulation (MSPA, MSR, MST), and the 50% blue:50% red spectrum in the biosynthesis of photosynthetic pigments. In the third experiment, the root system reached greater lengths with higher intensities and lower nitrogen concentrations. The stem diameter of the seedlings was also better developed as the light intensity increased, regardless of the salt concentration. Increasing the concentration of NH4NO3 and KNO3 salts reduced root dry mass accumulation. The highest averages of the photosynthetic pigments were obtained when subjected to the highest light intensity, in all nitrogen concentrations. At intensities 70, 113 and 144 μmol m−2 s−1 there was the highest total dry mass production. Culture medium with 200% of the Ca and Mg strength of DM and pH 5.5 favored the highest production of dry mass.